EDUKASI KEPERAWATAN PADA PASIEN TUBERKULOSIS DENGAN MENGGUNAKAN PENDEKATAN MODEL SELF-CARE OREM DAN TINDAKAN BERBASIS EVIDANCE BASED EDUKASI AUDIO VISUAL PURSED LIPS BRETHING - Irawan, Muhammad Henrie (Jurnal Abdi Mahosada, 2023)
Tuberculosis (TB), which is caused by Mycobacterium tuberculosis (MTB), is the leading cause of death from infectious diseases globally. Respiratory symptoms caused by TB are dry cough that gradually becomes productive for more than 3 weeks, sometimes mixed with phlegm, chest pain and dyspnea, for direct training it might be difficult to demonstrate pursed lib breathing practice, so the choice is yes, you can use audio visual media.). Evidence-based nursing that is applied during residency practice is pursed lib breathing education in MDR TB patients who experience dyspnea. The condition of Dipsnea experienced by MDR TB patients will make the patient no longer able to carry out the role they have and need help and support so that the nursing theory approach of the Orem Supportive-educative system self-Care model is very suitable for use in nursing care for MDR TB patients with Dipsnea complaints. The strategy that can be applied is in quadrant I or an aggressive strategy, namely a strategy to maximize the strengths and opportunities possessed by Aji Muhammad Parikesit Hospital. training for 50 new BLUD nurses in independent nursing follow-up Audio Visual Education Pursed Lip Breathing Exercise Audio Visual Education service activities Pursed Lip Breathing Exercise, nurses are able to improve the Pursed Lip Breathing Exercise Audio Visual Education process continuously, and nurses can carry out their duties optimally and professionally safely and comfortably, so nurses can focus on providing nursing care to patients respective rooms.